The effectiveness of community ageing in place, advancing better living for elders as a biobehavioural environmental approach for disability among low-income older adults: a systematic review and meta-analysis. (18th April 2023) - Rahmati, Masoud; Keshvari, Maryam; Koyanagi, Ai; Yon, Dong K; Lee, Seung W; Shin, Jae I; Smith, Lee
Abstract: Background: community ageing in place, advancing better living for elders (CAPABLE), which is a biobehavioural environmental approach by addressing individual capacities and the home environment, aims to reduce the impact of disability among low-income older adults. Objective: this meta-analysis aims to elucidate the efficacy of the CAPABLE program on related outcomes in low-income older adults. Methods: a systematic search of MEDLINE/PubMed, CINAHL and EMBASE was conducted for articles published up to August 2022. A systematic review and meta-analysis were performed to calculate the pooled effect sizes of the efficacy of the CAPABLE program on home safety hazards, activities of daily living (ADLs), instrumental ADLs (IADLs), depression, falls efficacy, pain and quality of life. Results: seven studies involving 2, 921 low-income older adults (1, 117 as the CAPABLE group and 1, 804 served as a control) with an average age ranging from 65 to 79 were included in the present meta-analysis. Pre–post effect analyses showed that CAPABLE was significantly associated with lower home safety hazards, ADLs, IADLs, depression, falls efficacy, pain and quality of life. Additionally, there were statistically significant associations between the CAPABLE program with improvements in ADLs, IADLs and quality of life compared with controls. Conclusion: CAPABLE intervention may be a promising strategy to reduce health disparities, and disability limitations, and improve the quality of life in low-income community-dwelling older adults who suffer from disabilities by addressing both the person and the environment.